Spinal Muscular Atrophy: A Systematic Review of Diagnosis, Treatment and Emerging Research (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
This systematic review aims at understanding the causes, consequences and therapy of spinal muscular atrophy, which is an inheritable illness which can be fatal at times. Although spinal muscular atrophy is incurable, various drugs have been developed to ameliorate the disease condition and this article aims at understanding the effect of all the available synthetic drugs on Spinal muscular atrophy (SMA). A search plan was curated using various databases like, PubMed, Google Scholar and Science Direct. Authors selected publications of Risdiplam, Onasemnogene abeparvovec and Nusinersen, and even studies comparing the drugs with one another, including studies related to drugs like hydroxyurea, phenylbutyrate and gabapentin. 40 publications were identified and finalized based on preferences. All the 3 approved drugs improved motor milestones in SMA patients as compared to natural cohort of the disease. Although Gene replacement therapy observed tremendous results, further investigations is needed to be done. Other drugs like hydroxyurea (HU), Gabapentin, Valproic acid and phenylbutyrate showed significant, little and no effect respectively. All 3 drugs showed significant outcomes and were safe and effective in the longer duration of use. Hydroxyurea and Valproic acid showed slight improvement whereas Gabapentin and Phenylbutyrate had no effect.